2021
DOI: 10.1371/journal.pone.0246661
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating changes in the prevalence of female genital mutilation/cutting among 0-14 years old girls in Nigeria using data from multiple surveys: A novel Bayesian hierarchical spatio-temporal model

Abstract: Female genital mutilation/cutting (FGM/C) is considered a public health and human rights concern, mainly concentrated in Africa, and has been targeted for elimination under the sustainable development goals. Interventions aimed at ending the practice often rely on data from household surveys which employ complex designs leading to outcomes that are not totally independent, thus requiring advanced statistical techniques. Combining data from multiple surveys within robust statistical framework holds promise to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…18 Some researchers argued that the practice of FGM continues because of social and family pressure to adhere to tradition, and this is passed on from generation to generation, whose result leaves girls and women to suffer the consequences indefensibly. 19 Other studies have also argued that the practice of FGM is sustained from generation to generation because the procedure is deeply rooted in social norms, cultural beliefs, and tradition or because of its strong association with ethnicity and religion, particularly among the Muslim community. 17,19 Although the practice of FGM in Nigeria is widespread and varies with geopolitical zone, state, and ethnic group, 13 several studies have reported that the highest prevalence of FGM is in the southern geopolitical zone of Nigeria, among the Yoruba and Igbo ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Some researchers argued that the practice of FGM continues because of social and family pressure to adhere to tradition, and this is passed on from generation to generation, whose result leaves girls and women to suffer the consequences indefensibly. 19 Other studies have also argued that the practice of FGM is sustained from generation to generation because the procedure is deeply rooted in social norms, cultural beliefs, and tradition or because of its strong association with ethnicity and religion, particularly among the Muslim community. 17,19 Although the practice of FGM in Nigeria is widespread and varies with geopolitical zone, state, and ethnic group, 13 several studies have reported that the highest prevalence of FGM is in the southern geopolitical zone of Nigeria, among the Yoruba and Igbo ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…19 Other studies have also argued that the practice of FGM is sustained from generation to generation because the procedure is deeply rooted in social norms, cultural beliefs, and tradition or because of its strong association with ethnicity and religion, particularly among the Muslim community. 17,19 Although the practice of FGM in Nigeria is widespread and varies with geopolitical zone, state, and ethnic group, 13 several studies have reported that the highest prevalence of FGM is in the southern geopolitical zone of Nigeria, among the Yoruba and Igbo ethnic groups. 4,16,20,21 This is consistent with our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely practiced in several African and Asian countries for cultural, traditional, hygienic, and religious beliefs affecting about 125 million girls under fifteen 4 . It was reported that women who underwent FGM had psychosocial disabilities, sexual embarrassment, and low quality of life, impacting their psychological and physical well-being 5 .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that women who underwent FGM had psychosocial disabilities, sexual embarrassment, and low quality of life, impacting their psychological and physical well-being 5 . Thus, in addition to violating a fundamental human right, FGM also leads to anxiety, depression, and social isolation 3 , 4 . Furthermore, it is also associated with short-term and long-term complications, including bleeding, infection, dermoid cysts and abscesses, chronic pelvic pain, recurrent urinary tract infections, difficulties in menstruation, maternal and fetal issues, and dyspareunia 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the statistical approach used in this paper, there are many potential advantages of this approach over more conventional approaches like discrete-time Cox models with time varying covariates and fixed or random districts effects; or standard 2-level multilevel modelling with unstructured spatial effects [22,23]. In the conventional models, it is assumed that the random components at the contextual level (province in our case) are mutually independent.…”
Section: Discussionmentioning
confidence: 99%